Assessment of Nutritional Status Based on STRONGkids Tool in Iranian Hospitalized Children - Gholampour, Zahra; Hosseininasab, Mina; Khademi, Gholamreza; Sezavar, Majid; Abdollahpour, Nooshin; Imani, Bahareh (International Journal of Child Health and Nutrition, 2015)
Background & Objective: Malnutrition is very common in hospitalized children and is associated with related clinical consequences such as increased risk of infections, increased muscle loss, impaired wound healing, longer hospital stay and higher morbidity and mortality. The estimated prevalence of acute malnutrition in hospitalized children varies from 6.1 to 40.9% in different countries. The current study was conducted with the aim of evaluating the efficiency of STRONGkids (Screening Tool for Risk On Nutritional Status and Growth) tool for assessing malnutrition in hospitalized children in Iran. Methods: All children older than 28 days admitted to the pediatric hospital (Dr. Sheikh, Mashhad, Iran) were enrolled in this study and the screening tool named STRONGkids was applied for them. The anthropometric measurements were measured by a trained operator using standard methods and equipments. The children were classified in three groups of being at high risk, moderate risk and low risk of malnutrition. Results: According to STRONGkids score; 17% of children were classified as low risk, 75% as moderate risk and 8% as high risk group. According to WFH, HFA and WFA z-scores31.4%, 19.2% and 28% of children were identified as moderately and severely malnourished respectively. According to MUAC cut-offs, 3.4% of children were classified as having moderate malnutrition and there was no child with severe malnutrition. Conclusion: It is very important to recognize the nutritional status of the children as early as possible because of its effects on children’s growth. Therefore, evaluating the nutritional status of the hospitalized children is an essential step in clinical assessment. We suggest to apply the STRONGkids score aside with other clinical and anthropometric data.